2012
DOI: 10.1136/bmjopen-2012-000864
|View full text |Cite
|
Sign up to set email alerts
|

The Nordic Patient Experiences Questionnaire (NORPEQ): cross-national comparison of data quality, internal consistency and validity in four Nordic countries

Abstract: ObjectivesTo evaluate the Nordic Patient Experiences Questionnaire (NORPEQ) for data quality, reliability and validity following surveys of patients in Finland, Norway, Sweden and the Faroe Islands.Design, methods and participantsThe NORPEQ was mailed to 500 patients randomly selected after receiving inpatient treatment in Finland, Norway and Sweden. The NORPEQ was also included in a national survey in Norway and in the Faroe Islands. Dimensionality was assessed using principal component analysis and internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 37 publications
2
48
0
1
Order By: Relevance
“…Patient responses to experience surveys are frequently dominated by the most positive response option. [29][30][31][32] However, research using qualitative approaches indicates that experiences may in fact be poorer than those suggested through literal interpretation of the labels of quantitative surveys. 8 9 Patients may be reluctant to criticise care using survey instruments, a phenomenon that has previously been reported in users of mental health services, and in patients undergoing elective orthopaedic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Patient responses to experience surveys are frequently dominated by the most positive response option. [29][30][31][32] However, research using qualitative approaches indicates that experiences may in fact be poorer than those suggested through literal interpretation of the labels of quantitative surveys. 8 9 Patients may be reluctant to criticise care using survey instruments, a phenomenon that has previously been reported in users of mental health services, and in patients undergoing elective orthopaedic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Skudal et al in four Nordic countries showed that the least patient satisfaction was related to administrative and financial units and the highest satisfaction was from public and welfare services. Also determining factors for dissatisfaction and attempt to solve them and identify and correct some hospital processes, especially the processes of acceptance and discharge are among cases that in addition to making it possible to provide services with higher quality, leads to patient satisfaction [15]. Riiskjaer et al in a study in 2012 observed strong positive correlation between the index of hospital environment and patient satisfaction.…”
Section: Resultsmentioning
confidence: 97%
“…Through face-to-face meetings, the contents of some questionnaires used in previous surveys in English-speaking countries and in Italy were reviewed, including provision of information on the visit and treatment course, humanization of care, outpatient involvement in decision making, perception of competence, management of continuity of care, privacy, and overall satisfaction. In particular, the following multidimensional and unidimensional questionnaires were examined: the Picker Patient Experience Questionnaire35 developed by Gasquet et al,22 the Nordic Patient Experience Questionnaire,25 and the questionnaire developed by Oltedal et al24 for foreign contexts: the Quality Perception Questionnaire31 and the Verona Satisfaction Scale27 for the Italian context. In addition, some reviews and papers on theoretical models of patient-centeredness were examined 16…”
Section: Methodsmentioning
confidence: 99%